Analisa Pembebanan Statis Rangka Scooter Listrik Menggunakan Software Autodesk Inventor - Kurnianto, Herlambang Rizky; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstract Electric scooters have become a popular choice for urban transportation in many cities. This research focuses on the influence of frame materials on stress and deformation in electric scooters. The study uses carbon steel and galvanized steel, with testing conducted using Autodesk Inventor 2022 Professional Student. The support points on the electric scooter frame and load distribution when the rider is in a normal sitting position are considered. The support points are located at the top of the front fork and at the rear wheel support. The research aims to analyze the impact of using different frame materials on the deformation behavior due to rider loading. In static loading simulations, the use of low carbon steel for the electric scooter frame resulted in a Von Mises stress of 21.2 MPa, a displacement of 0.4207 mm, and a safety factor of 15. Meanwhile, the use of galvanized steel produced a Von Mises stress of 21.12 MPa, a displacement of 0.4201 mm, and a safety factor of 9.8. The difference in these results indicates that the frame made of low carbon steel has higher reliability and can withstand loads better compared to galvanized steel. It can be concluded that the low carbon steel frame has nearly the same Von Mises stress as the galvanized steel frame but has slightly higher displacement. More importantly, the low carbon steel frame has higher safety factors compared to the galvanized steel frame. Keywords: scooter, frame, von mises stress, simulation, autodesk inventor